PROCESSING AND PROPERTIES OF AL2O3/SIC NANOCOMPOSITES - Borsa, C; Jiao, S; Todd, R; Brook, R (1995)
Alumina/SiC nanocomposites were produced by mechanical mixture of commercial powders. The preparation steps involved the vigorous mixing of the powders and drying under conditions where the homogeneous mixture was kept stable, Pressureless sintering of die-pressed powders achieved reasonable densities (similar to 97% theoretical density) for 2.5wt% of SiC on sintering at 2073K. Higher SIC contents strongly reduced the sintered density. The use of a more reactive alumina (finer matrix powder) gave similar results, Hot pressing at 1973 K/1 h/25 MPa produced high-density materials for SiC contents Bs high as 20 wt%. Transmission and scanning electron microscopy analysis showed that the SiC particles were well distributed and were situated both inside the grains and on the grain boundaries of the alumina matrix, The SiC strongly inhibited grain growth in the matrix in keeping with the Zener model. The bend strength increased as the SiC content increased, a result partly explained by the grain size refinement. The strength improvement of 20% over monolithic was explained In terms of the change to an intergranular fracture mode.